The Effect of Straw, Rope, and Bite-Rite Treatment in Weaner Pens with a Tail Biting Outbreak - Helle Pelant Lahrmann; Julie Fabricius Faustrup; Christian Fink Hansen; Rick B. D’Eath; Jens Peter Nielsen; Björn Forkman (Animals, 2019)
Tail biting in pigs is an injurious behaviour that spreads rapidly in a group. We investigated three different treatments to stop ongoing tail biting outbreaks in 65 pens of 6−30 kg undocked pigs (30 pigs per pen; SD = 2): (1) straw (7 g/pig/day on the floor), (2) rope, and (3) Bite-Rite (a hanging plastic device with chewable rods). Pigs were tail scored three times weekly, until an outbreak occurred (four pigs with a tail wound; day 0) and subsequently once weekly. After an outbreak had occurred, a subsequent escalation in tail damage was defined if four pigs with a fresh tail wound were identified or if a biter had to be removed. Straw prevented an escalation better (75%) than Bite-Rite (35%; p < 0.05), and rope was intermediate (65%). Upon introduction of treatments (day 0), pigs interacted less with tails than before (day −1; p < 0.05). Behavioural observations showed that pigs engaged more with rope than Bite-Rite (p < 0.05). Bite-Rite pigs (but not straw or rope) increased their interaction with tails between day 0 and day 7 (p < 0.05). Straw was the most effective treatment. However, further investigations may identify materials or allocation strategies which are more effective still.